Incidence and clinical profile of tuberculosis after allogeneic stem cell transplantation. Issue 1 (26th November 2017) - Agrawal, Narendra; Aggarwal, Mukul; Kapoor, Jyotsna; Ahmed, Rayaz; Shrestha, Anjan; Kaushik, Meena; Bhurani, Dinesh
Abstract: Background: Patients post allogeneic stem cell transplantation (alloSCT) are expected to be at high risk of tuberculosis (TB) owing to underlying immunosuppression. We conducted a retrospective study in patients post alloSCT for clinical features and factors associated with TB. Methods: Records of all patients transplanted from January 1, 2012 until December 31, 2015 were reviewed. Diagnosis of TB was considered if Mycobacterium tuberculosis was cultured from clinical samples or acid‐fast bacilli (AFB) were demonstrated on histopathology/smears. A presumptive TB diagnosis was considered in the presence of signs and symptoms suggestive of TB with epithelioid cell granulomas, without AFB. Results: In 175 eligible patients, TB was detected in 5 patients (pulmonary = 4, lymph node = 1), with incidence of 2.84% at median of 258 (157‐639) days after transplantation. Cumulative incidence rate of TB among the patients undergoing alloSCT was calculated to be 1.9/100 person‐years. Median duration of symptoms was 20 days till diagnosis was confirmed. All patients were started on four‐drug anti‐tubercular therapy (ATT) with clinical/radiological response in all. Two patients developed hepatotoxicity (transaminitis, n = 1; hyperbilirubinemia, n = 1) following ATT. Presence of chronic graft‐versus‐host disease (GVHD) ( P  = .008) and steroid‐refractory GVHD ( P  = .001) was found to be significantly associated with TB. Conclusion: TB should be suspected in patients with unexplained fever post alloSCT. Active GVHD and ongoing immunosuppression/steroids are possible risk factors. Early diagnosis and treatment can salvage most patients. Hepatotoxicity following ATT is a potential concern.